Participation Of Participants In The Savings And Loan Program And Its Relationship To Farming Financing At Farmer Women Group (KWT) Tani Mulyo - Dewi Lestari, Retna; Rahyunanto, Setyo; Fajeri, Sari (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
The KWT Tani Mulyo savings and loan program aims to help members finance in order to run their farming business. The existence of this program can help the community in improving the family economy through increasing family income. This research was conducted in the Mulyo Farmers Women Group (KWT) Karanganyar Village, Sambungmacan District, Sragen Regency. The method used in this study is descriptive. The data used is primary data and secondary data. The savings and loans program (KWT) has been able to help members and administrators in fulfilling business capital and basic living needs, which has an effect on improving the economy. The savings and loan program has regulations that regulate the mechanism and requirements for savings and loans. Members or administrators who participate in the program every month during regular meetings are allowed to save money or save with a free amount without special provisions, while members who are borrowing money have a provision that every month they are required to pay installments of a predetermined interest rate of 3%. The importance of understanding savings and loans for members so that in the future they can be used according to their proportions and needs